Penerapan Akuntansi Tingkat Harga Dasar pada Perusahaan Umum Daerah Air Minum Kota Makassar - Zulfaida Ahmad; Sahabuddin; Sri Rahyuni (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
This study aims to analyze the application of Basic Price Level Accounting in the Regional Drinking Water Company (Perumda Air Minum) of Makassar City during the 2021–2023 period. The research uses a qualitative descriptive approach with primary and secondary data obtained from financial statements, observations, documentation, and interviews. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, focusing on liquidity, solvency, and profitability ratios after price level adjustments. The results show that price level adjustments provide a more realistic representation of the company’s financial condition, particularly in reflecting changes in purchasing power due to inflation. Liquidity remains strong, solvency shows a declining trend that requires attention, and profitability indicates improved investment efficiency with fluctuating returns to equity. This study contributes to improving the accuracy of financial analysis for public sector enterprises under inflationary conditions.